Corporate Governance Moderation on the Influence of Business Environmental Uncertainty on Capital Structure - Ningsih, Fitria Ayu; Hariyati, Hariyati (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The uncertainty of the business environment due to economic dynamics, regulations, and global markets requires companies to be adaptive, including in capital structure decisions. This study examines the effect of business environmental uncertainty on capital structure, as well as the role of corporate governance as a moderating variable. Using a quantitative approach with multiple linear regression and moderated regression analysis (MRA), data were collected from 72 manufacturing companies listed on the IDX for the period 2021–2023. The results show that environmental uncertainty has a significant negative effect on capital structure, while corporate governance is proven to weaken this negative effect. This means that a good supervisory mechanism can help companies manage risk and maintain capital structure stability. These findings strengthen contingency and agency theories and suggest the importance of effective governance as a financial risk mitigation strategy.